Reliability Assessment Of Self-Alignment Assemblies Of Chip Component After Reflow Soldering Process - Ali Mokhtar, Mohd Najib; Abdullah, Mohd Zulkifly; Saad, Abdullah Aziz; Che Ani, Fakhrozi; Samsudin, Zambri (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
Reliability of surface mount components and interconnect are significant issues in electronic manufacturing. Although the reliability of devices has been broadly studied,here we are focusing on the reliability of the solder joint after the self-alignment phenomena during reflow soldering.In this study,the quality of the self-alignment assemblies was analyzed relate to the joint shear strength according to the JIS Z3 198-7 standard and the inspection according to IPC-A-610E standard.The results from reliability study indicate that the shear strength of the misalignment component of solder joints indeed depends on the degree of chip component misalignment.For shift mode configuration in the range of 0-300µm,the resulted chip assembly inspection after the reflow process was in line with the IPC-A-610E standard.